Reinforced Concrete Posts Made by Long-Line Formwork-Free Shaping for 0.4–10 kV Overhead Line Supports - P. T. Mirzaev; Z. P. Shamansurova (Наука и техника)
When using the technology of long-line formwork-free shaping for the manufacture of reinforced concrete structures, industrial engineering can be conducted in accordance with the requirements of modern regulatory documents. This allows projects to be developed individually, and production lines can be readjusted in a short time in accordance with emerging needs. In this regard, the possibility of using reinforced concrete posts produced by the technology of long-line formwork-free shaping for 0.4-10 kV overhead line supports is being considered. The designs of such supports are developed on the standard basis of the product range. The problem of establishing the minimum number (two) of cross-sections with different geometric dimensions for all brands of the offered posts is solved, subject to the operational requirements and technological specifications of production. The cross-sections of the proposed posts represent trapeziums, with the dimensions of the upper bases smaller than the dimensions of the lower bases in order to maintain the shape of the freshly formed concrete body of the posts made using long-line formwork-free shaping technology. For posts up to 11.0 m long, a solid cross-section with trapezoid edges is proposed: h = 245 mm; b = 150 mm (an upper base); b1 = 180 mm (a lower base). In the middle part of the cross-section of posts with a length of 11.0 to 16.4 m there is a cavity along the entire length of the posts. Cross-sectional dimensions of such posts are h = 300 mm; b = 205 mm, b1 = 235 mm. Long-line formwork-free shaping technology provides for the reinforcement of prestressed structures with high-strength wire or rope reinforcement. The proposed posts are rein-forced with 5Вр1400 rods, therefore, during their operation, the formation of cracks in the tensile zone of concrete is not fore-seen. The rods are located in groups at all corner sections along the cross-section of the post with an equal number of rods in each group, taking into account the technological features of the long-line formwork-free shaping. For the proposed cross-section of hollow posts, produced by long-line formwork-free shaping for 0.4–10 kV overhead line supports, a patent for autility model has been obtained from the Agency for Intellectual Property of Uzbekistan. Qualitative characteristics of the posts for overhead line supports are low material consumption, versatility, manufacturability, innovation, which lies in the fact that their implementation is associated with the design, manufacture and testing of experimental products for use by specific consumers, i. e. with the commercialization.